A CONTRIBUIÇÃO DA ANÁLISE DE REDES SOCIAIS NA IDENTIFICAÇÃO DOS CONHECIMENTOS CRÍTICOS EM UMA ORGANIZAÇÃO: UM ESTUDO DE CASO - Formanski, José Gilberto (2011)
The structures represented by the formal organization chart does not reflect the real flow of information within an organization. Are the informal networks that have played a key role in obtaining general information and work towards achieving the important processes in organizations. In order to better understand the flow of information through these informal networks and their contribution to the criticality of strategic knowledge, maps can be developed to illustrate the actual flow of information and the location of the critical knowledge in the network. The social network analysis is a technique that can be applied in the construction of knowledge maps to help analyze the strengths and weaknesses of informal networks effectively. This document provides a case study to illustrate the application of social network analysis to develop and analyze knowledge maps for a team of automation engineering.